Analisis Kandungan Logam Berat Fe, Ni, Pb, dan Cr di Kawasan Muara, Mangrove, dan Green Canyon Sungai Cijulang di Pangandaran - Putri, Rizkya Dwiananda; Rofilah, Salsazahra; Susetyo, Eprafoditus Kristiadi; Ma’ruf, Nardyawan Arifi; Kevin, Kevin; Solikah, Al Milatus; Pinandita, Aria; Putra, Mochamad Resya; Azis, Muhammad Yudhistira (Jurnal Kartika Kimia, 2024)
One of the main natural resources of living things is water. Water quality is a parameter that determines the function of water. This gives urgency in conducting research related to water quality analysis. Water with good qualities has many essential functions for life. However, water contamination due to anthropogenic activities and natural phenomena is unavoidable. The most common contaminants are heavy metals. Analysis of the content of heavy metals such as Fe, Ni, Cr, and Pb was carried out in samples of Cijulang River water in three zones, namely estuaries, mangroves, and green canyons using the Atomic Absorption Spectrophotometry (AAS) method. Data acquisition was further analyzed with statistical visualization tests in the form of boxplots and bar charts, as well as non-parameter tests in the form of the Kruskal-Wallis test and the Friedman test. Analysis with boxplots shows that the results of the data have a high distribution. Analysis using bar charts shows that most of the data exceeds the Class I quality standard. Analysis using the Kruskal-Wallis test and Friedman test obtains a p-value of 0.3916 for the Kruskal-Wallis test and 0.7788 for the Friedman test. This value indicates that the median of the three data is assumed to be the same. Based on the Regulation of the Minister of Health Number: 416 / MENKES / PER / IX / 1990 concerning Requirements and Quality Control, the quality standard for Cijulang River water samples is classified as Class II.